2017
DOI: 10.1039/c7nr05737g
|View full text |Cite
|
Sign up to set email alerts
|

One dimensional building blocks for molecular separation: laminated graphitic nanoribbons

Abstract: Herein, a new carbon-based graphitic membrane composed of laminated graphitic nanoribbons with a nanometer-scale width and micrometer-scale length, the graphitic nanoribbon membrane, is reported. Compared to the existing graphitic membranes, such as those composed of graphene oxide and carbon nanotubes, the developed membrane exhibits several unique characteristics in pressure-driven systems. First, the short diffusion length through its interlayer and the free volume of its stacked nanoribbons result in high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…This reduction is evident because the filtered dye blocks channel entry on the membrane surfaces. 28,29 The rejection rates of the dye solutions (MR, MnB, BBG, EB, and RosB) were 93.2, 99.9, 98.2, 87.8, and 96.6% for the slot-die coated Ti 3 C 2 T x membranes and 77.9, 86.3, 94.2, 46.2, and 97.9% for the vacuum-filtered Ti 3 C 2 T x membranes, respectively (Figure 4B), indicating the better separation ability of the slotdie-coated membrane. The inset images show the solutions before and after filtration: F is feed, V is permeate of the vacuumfiltered membrane, S is permeate of the slot-die-coated membrane.…”
Section: Resultsmentioning
confidence: 99%
“…This reduction is evident because the filtered dye blocks channel entry on the membrane surfaces. 28,29 The rejection rates of the dye solutions (MR, MnB, BBG, EB, and RosB) were 93.2, 99.9, 98.2, 87.8, and 96.6% for the slot-die coated Ti 3 C 2 T x membranes and 77.9, 86.3, 94.2, 46.2, and 97.9% for the vacuum-filtered Ti 3 C 2 T x membranes, respectively (Figure 4B), indicating the better separation ability of the slotdie-coated membrane. The inset images show the solutions before and after filtration: F is feed, V is permeate of the vacuumfiltered membrane, S is permeate of the slot-die-coated membrane.…”
Section: Resultsmentioning
confidence: 99%
“…For the dried GONR, the (001) peak is observed at 11.2°, regardless of its concentration, indicating the stacking of GONRs after the removal of water. The broad XRD peak of the GONR at 2θ of 11.2° is due to its narrow width (50–75 nm) and the presence of oxygen functional groups, which hinder the narrow stacking between the basal planes of GONRs. , However, the (001) peak is not observed in the as-prepared GONR hydrogel (50 mg/mL), which only shows a peak at 27.4° owing to the multilayered structure of the GONR hydrogel (Figure S1). , Therefore, while GONRs are physically entangled in their assembled structures in the suspension, the surrounding water molecules and electrostatic repulsion by oxygen functional groups effectively prevent the physical stacking of the GONR layers.…”
Section: Resultsmentioning
confidence: 99%
“…Graphene nanoribbon (GNR), a nanostrip of graphene, has recently been used widely for energy storage, nanocoatings, fiber formation, membrane separation, sensors, etc . owing to its chemical and physical properties such as a controllable band gap, large surface area, electrical conductivity, and chemical stability and so forth. , However, there is still a lack of the understanding of the structure and viscoelastic behavior of GNR in solvents, although many studies have been reported on those of GO and CNTs. Herein, we report the preparation of aqueous GONR (graphene oxide nanoribbon) hydrogels and a systematic study of their rheological properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to GO nanosheets, GO nanoribbons (GONRs) are one-dimensional graphitic carbon nanosheets that can be fabricated by the oxidation of carbon nanotubes (CNTs). Kim et al first suggested the use of laminated GONR membranes for molecular separation in water and various organic solvents [78]. Regardless of membrane thickness, this membrane, prepared by simple vacuum filtration, exhibited a significantly higher water flux than the normal GO membrane, owing to the short diffusion pathway through the laminates and free volume between the entangled nanoribbons (Figure 7a).…”
Section: Graphene Nanoribbon Membrane (Nanopore Made Of Entangled Gn Nanoribbons)mentioning
confidence: 99%